Training in nutritional counseling: knowledge assessment and applicability in child's healthcare - Claudia Nery Teixeira Palombo; Elizabeth Fujimori; Áurea Tamami Minagawa Toriyama; Luciane Simões Duarte
Abstract Objectives: to assess the primary healthcare professionals' knowledge before and after the training in nutritional counseling and the applicability in child's healthcare. Methods: a non-controlled 'before and after' intervention study, in a quantitative approach was conducted in Itupeva city in, Sao Paulo State. Training as an intervention was implemented for nurses, nursing assistants (NA) and community health agents (CHA), based on the critical-reflexive education. The professionals' knowledge was evaluated by applying a test with 16 multiple choice questions before and after the training. The nutritional counseling applicability in the services was evaluated by an open question test. The descriptive statistics and Fisher's Exact Test with significance of 5% were used Results: after training, the 'satisfactory' knowledge increased 71% in the nurses group and the NA/CHA groups. The professionals pointed out that training as an opportunity for qualification but the applicability lacks on political support and service organization. Conclusions: training in nutritional counseling contributes to expand the primary care professionals' knowledge, although, the applicability in the routine depends on the efforts of local management and service organization.